2011
DOI: 10.1111/j.1477-2574.2011.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative computed tomography measurements of pancreatic steatosis and visceral fat: prognostic markers for dissemination and lethality of pancreatic adenocarcinoma

Abstract: In resected pancreatic adenocarcinoma, increased pancreatic steatosis and increased visceral fat stores are associated with lymphatic metastases. Furthermore, increased visceral fat is associated with abbreviated survival in patients with lymphatic metastases. Hence, increased visceral fat may be a causative factor of abbreviated survival and serves a prognostic role in patients with pancreatic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 33 publications
(76 reference statements)
1
61
0
Order By: Relevance
“…In stark contrast, no difference was noted in the subcutaneous fat pad. 16 Balentine et al 31 confirmed are findings showing that visceral fat and not BMI was associated with a worse overall survival.…”
Section: Commentsmentioning
confidence: 90%
See 3 more Smart Citations
“…In stark contrast, no difference was noted in the subcutaneous fat pad. 16 Balentine et al 31 confirmed are findings showing that visceral fat and not BMI was associated with a worse overall survival.…”
Section: Commentsmentioning
confidence: 90%
“…Epidemiologic evidence suggests that the relative risk of pancreatic cancer increases by 1.12 for every 5-point increase in BMI. 16 Furthermore, patients with a BMI greater than 35 have a 45% greater risk of development of pancreatic cancer. 13 Additionally, Mathur et al have demonstrated that obesity is associated with a worse prognosis from hepato-pancreatico-biliary cancers.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, pancreatic steatosis is associated with heightened PDAC risk and plays a negative prognostic role in patients with PDAC ( 1,2 ). Starting from previously published data showing that obesity increases the proinfl ammatory cytokine IL1β and fuels an infl ammatory milieu associated with accelerated tumor growth and metastasis formation, Incio and colleagues show that obesity shapes a distinctive PDAC microenvironment characterized by adipocyte accumulation and hypertrophy, local cross-talk between tumor-associated neutrophils (TAN) and PSCs, and the production of proinfl ammatory and profi brotic factors, which in turn favor tumor progression and severely limit the delivery of chemotherapeutic drugs ( 3 ).…”
mentioning
confidence: 99%